Terapias de reemplazo renal en la intoxicación por litio y su adecuación a los criterios del consenso EXTRIP: estudio multicéntrico SILITOX. - Pineda-Torcuato, Álvaro; Caballero-Bermejo, Antonio F.; Supervía, August; Salgado, Emilio; O'Laoi, Ruadhan; Sánchez, Carolina; Córdoba, Francisca; Rodríguez Farré, Neus; Sanz-López, Natalia; Hernández Ontiveros, Héctor; Gallardo Sánchez, Blanca Andrea; Romero Gallardo, Paula; et al. (Emergencias, 2026)
Objectives. To evaluate adherence to the recommendations of the EXTRIP (Extracorporeal Treatments In Poisoning) group for the indication of renal replacement therapy (RRT) in patients with lithium poisoning, determine factors associated with the use of this therapeutic method, and analyze its impact on clinical outcomes. Methods. Multicenter international observational study including all episodes of lithium poisoning treated from 2015 through 2022 in emergency departments (ED) and clinical toxicology units (CTU) of 23 tertiary referral centers in Spain, Ireland, and Switzerland. Events were retrospectively classified according to EXTRIP criteria as RRT recommended, suggested, or not recommended. Adherence to these recommendations and their association with clinical outcomes were analyzed using uni- and multivariate analyses. Results. A total of 548 episodes of lithium poisoning were analyzed, of which 119 (21.7%) received RRT. According to EXTRIP criteria, RRT was recommended in 161 episodes (29.4%), suggested in 137 (25%), and not recommended in 250 (45.6%). Overall adherence to EXTRIP was 77.2%, and 69.6% when considering only strict indications. No significant differences were observed between adherent and non-adherent groups in the incidence of SILENT (Syndrome of Irreversible Lithium-Effectuated Neurotoxicity) at 60 days (7.1% vs 5.6%), need for critical care admission (16.8% vs 16.1%), or in-hospital mortality (3.3% vs 5.6%). Peak lithium concentration [3.45 (SD, 1.53) vs 2.05 (SD, 0.71) mEq/L; P < .001], decreased level of consciousness [49 (41.2%) vs 92 (21.4%); P < .001], and presence of atrioventricular block [6 (5.0%) vs 5 (1.2%); P = .008] were independent predictors for performing RRT. Conclusions. Adherence to EXTRIP recommendations was moderate to high but was not associated with improved clinical outcomes. These findings support an individualized approach based on clinical assessment when indicating RRT and suggest the need to refine EXTRIP criteria to improve applicability in real-world practice.